The Study of Conditional Probability Matrix for Realive Pair Genotypes - He, Chaobing (International Journal For Research In Mathematics And Statistics, 2021)
This paper considers the conditional probability matrix for realive pair genotypes. First this paper systematically introduces HardyWeinberg equilibrium law, the joint probability distributions for relative pair genotypes and the ITO method. Then this paper discusses the calculation of probability distribution of the number of identical-by-descent allele of relative pairs, and lists the probabilities in tables. The paper gives the definition of quasi conditional probability matrix for the realive pair genotypes, and obtains a conclusion about quasi conditional probability matrix.